Hubungan Antara Kemampuan Menggunakan Adawat Al-Rabth Dengan Kemampuan Insya - Muyasaroh, Wildatul (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
One of the Arabic language skills is writing skills. Writing skills are considered the most difficult Arabic language skills because students must have sufficient Arabic language skills, one of which is having the ability to use Adawat Al-Rabth correctly. This research aims to determine the relationship between the ability to use Adawat al-Rabth and the ability to Insha’. The method used in this research is quantitative with an associative relationship test type. The research population was students of Arabic Language Education at Syarif Hidayatullah State Islamic University, Jakarta. Sampling was carried out using a purposive sampling technique with a sample size of 50 people. The instruments used to obtain data were a written test to determine insha’ ability and a questionnaire with a Likert scale to determine ability to use Adawat al-Rabth. Data analysis uses a correlation formula to determine the relationship between the ability to use Adawat al-Rabth and the Insha’ ability of students. The results of the correlation test show that there is a relationship between the two variables, where the correlation coefficient value is 0.674, indicating that there is a "moderate relationship" between the two. This means that the better the students’ ability to use Adawat al-Rabth, the better their insha’ abilities will be. These findings produce knowledge for Arabic language teachers that students’ proficiency in writing Arabic is influenced by their ability to use Adawat Al-Rabth.